Symbolic use of traditional architectural features on contemporary mass housing facade in North Cyprus - Dastjerdi, Mojtaba Sokhanvar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: House as an important part of humans’ life is able to have a huge impact on its residents’ life quality. In fact, Housing as a fundamental category of architecture should be constructed by proper consideration on the residents’ cultural characteristics. In this respect, investigating on the traditional houses’ features of the particular region could led architects to use the competent features in contemporary houses. In this regard, using the traditional housing features in the symbolical form is the gainful approach to keep the bond between users and their modern houses. This thesis is tried to find the housing features in Cypriot traditional houses which is used symbolically in contemporary mass housing projects. For this aim, during the study it is attempted to learn the symbol explanation and its functions for discovering the symbolic features within selected mass houses. Moreover, two recent architectural periods of Cyprus (Ottoman and British Colonial) have been scrutinized for learning the Cypriot traditional housing features. Eventually, interviews results in addition to the physical observation have been led the study to reach the accurate result. Based on findings, this study achieved to discover some of traditional housing features which have been used symbolically in contemporary mass houses and they are demonstrated in conclusion. Keywords: Symbol, Housing, Mass housing, Contemporary mass housing facade, Cyprus traditional houses. ………………………………………………………………………………………………………………………… OZ: Ev, insanların hayatında önemli bir parçadır ve sakinlerinin yaşam kalitesi üzerinde büyük bir etkiye sahiptir. Aslında konut mimarlığın temel bir kategorisidir ve yerleşiklerin kültürel özelliklerine uygun şekilde inşa edilmelidir. Bu bağlamda, belirli bölgelerdeki geleneksel konutların özelliklerinin araştırılması, mimarların çağdaş tasarımlarda mimarların geleneksel özellikleri kullanmalarına ve tasarımda yansıtmalarına olanak sağlar. Bu bağlamda, sembolik biçimde geleneksel konut özelliklerinden yararlanmak kullanıcılar ve modern evler arasındaki bağı korumak için yararlı bir yaklaşımdır. Bu tez, çağdaş toplu konut projelerinde sembolik bir biçimde kullanılan Kıbrıs geleneksel evlerindeki detaylari bulmayı amaçlar. Bu amaçla, çalışma kapsamında sembol çalışma sırasında seçilen toplu konut içinde sembolik özelliklerini keşfetmek için sembolü açıklama ve fonksiyonları öğrenmek için çalışılır. Ayrıca, Kıbrıs’taki geleneksel evlerin özelliklerini öğrenirken son iki mimari dönemi (Osmanlı ve İngiliz sömürgesi) araştırıldı. Sonuç olarak, röportaj ve fiziksel izlenimler çalışmada doğru sonuçlara ulaşılmasını sağladı. Bulgulara dayanarak, bu çalışma çağdaş toplu konutlarda sembolik olarak geleneksel konut özelliklerinin kullanıldığını tespit etmiş ve bunlar sonuç bölümünde detaylıca ortaya konmuştur. Anahtar Kelimeler: Geleneksel mimari, Sembol, Konut, Toplu konut, Kuzey Kıbrıs Toplu konut.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Assist. Prof. Dr. Rafooneh Mokhtarshahi Sani.
Keywords: Architecture; Symbol, Housing, Mass Housing, Contemporary Mass Housing Facade, Cyprus Traditional Houses